THE ROLES OF JUDGES IN DEMOCRACIES: a realistic view - Leiter, Brian (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
What are the “obligations” of judges in democracies? An adequate answer requires us to be realistic both about democracies and about law. Realism about democracy demands that we recognize that electoral outcomes are largely, though not entirely, unrelated to concrete policy choices by elected representatives or to the policy preferences of voters, who typically follow their party based on “tribal” loyalties. The latter fact renders irrelevant the classic counter-majoritarian (or counter-democratic) worries about judicial review. Realism about law requires that we recognize that judges, especially on appellate courts, will inevitably have to render moral and political judgments in order to produce authoritative resolutions of disputes, one of the central functions of a legal system in any society. That means it is impossible to discuss the “obligations” of judges without regard to their actual moral and political views, as well as the moral and political ends we believe ought to be achieved.